Interlayers for Improved Hole Injection in Organic Field‐Effect Transistors - Ke Zhang; Naresh B. Kotadiya; Xiao‐Ye Wang; Gert‐Jan A. H. Wetzelaer; Tomasz Marszalek; Wojciech Pisula; Paul W. M. Blom (Advanced Electronic Materials, 2020)
Abstract Efficient charge‐carrier injection is a critical requirement for high‐performance organic electronic devices, such as light‐emitting diodes, solar cells, and field‐effect transistors. In this work, a significantly improved charge‐carrier injection from high work‐function metal‐oxide electrodes in organic field effect transistors (OFETs) is demonstrated for amorphous organic semiconductors (OSCs) by using organic interlayers with a high ionization energy (IE). Molybdenum oxide (MoO3) exhibits limited injection into amorphous 2,2′,7,7′‐tetrakis(N,N‐diphenylamino)‐9,9‐spirobifluorene (Spiro‐TAD) and tris(4‐carbazoyl‐9‐ylphenyl)amine (TCTA) active layers, resulting in high contact resistance and threshold voltage. By inserting an interlayer of a few nanometers thick with high IE between the MoO3 electrode and the amorphous OSC films, the Spiro‐TAD and TCTA OFETs show a substantial enhancement in hole current, subthreshold swing, and effective charge carrier mobility due to the decreased contact resistance. However, for discontinuous interlayers formed on distinct grain domains as in the case of polycrystalline 2,7‐dioctyl[1]benzothieno[3,2‐b][1]benzothiophene (C8‐BTBT) films, the effect of the interlayer reduces. These results demonstrate that the utilization of smooth interlayers with IE higher than the semiconductor is a general approach to elevate the hole injection into amorphous OSCs with high IE in OFETs.